Kepuasan Pelanggan Internal terhadap Kompensasi Finansial: Studi Kasus Layanan Klaim Asuransi Kesehatan - Fadia Ellisza; Dewi Khrisna Sawitri (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze internal customer satisfaction with health insurance claim services as part of indirect financial compensation in a national electricity provider organization. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis. The findings indicate that the claim process remains manual and faces several administrative challenges, including incomplete physical documentation, lack of transparency, and limited digital infrastructure. SERVQUAL analysis reveals that the five service quality dimensions—tangibles, reliability, responsiveness, assurance, and empathy—have not been optimally fulfilled, resulting in internal customer dissatisfaction. This dissatisfaction affects employee motivation, perceptions of organizational justice, and operational effectiveness. Therefore, service reform through process digitalization, enhanced proactive communication, and the development of a responsive and inclusive support system.